If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13(t-2)+8t=7(3t+5)-10
We move all terms to the left:
13(t-2)+8t-(7(3t+5)-10)=0
We add all the numbers together, and all the variables
8t+13(t-2)-(7(3t+5)-10)=0
We multiply parentheses
8t+13t-(7(3t+5)-10)-26=0
We calculate terms in parentheses: -(7(3t+5)-10), so:We add all the numbers together, and all the variables
7(3t+5)-10
We multiply parentheses
21t+35-10
We add all the numbers together, and all the variables
21t+25
Back to the equation:
-(21t+25)
21t-(21t+25)-26=0
We get rid of parentheses
21t-21t-25-26=0
We add all the numbers together, and all the variables
-51!=0
There is no solution for this equation
| k=8k=28 | | 4n+2=6(0.33n-0.66) | | -7x+33=-2(x+1) | | b-18/5=2b | | 5-10×c+8×c=10 | | (5-9m)/m^2-36=0 | | 2/3x−5=21 | | 8(4+x)=7(x-6) | | 3x-3=6x-48 | | 2x-1/3-x+1/4=4 | | 12w=-108 | | -8x+2x-16=-5x+7x | | 13n+16=-23 | | 190=-3x-4(5x+10) | | 6b^2=-8+6b | | -5-5(-3+n)=18-5n | | -5(y-2)=3y-30 | | 2/3(3x-12)=3/4(8x-12) | | 4x-3-x=30+3 | | (5/18)=(11/6)m+(1/2)+1 | | c+9/2=6 | | 10x-7-7x=53 | | (x*x+9)-(4x*x+16)=0 | | -4.3r=12.04 | | 2x=48=10x | | 206=14-y | | 2x-18=13+6 | | 3x+2+3=-6x+9-12 | | x/3-x/2=15 | | 88=(8983/45)r | | 0.1+j0.5÷21.78=0 | | -b-7=-7(1+4b) |